2021
DOI: 10.3390/en14040994
|View full text |Cite
|
Sign up to set email alerts
|

Government Incentive Contracts for Microgrid Users

Abstract: Tariff subsidies are beneficial to the further development of the microgrid market. In response to the reduction of the power generation costs of microgrids, the energy storage subsidy for microgrids has become a key factor affecting their further development. Therefore, it is essential to explore and establish a government subsidy mechanism for the energy storage price of microgrids. In this paper, we consider the incentive compatibility constraints and participation constraints of both the government and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…So TSO even will give subsidies to MGs. As a case study, [40] reports assigning subsidies to an energy storage project in China with a 5 MWh lithium and a 20 MWh lead-acid energy storage system. In our study, peak shaving and annual electricity cost reduction have been considered factors for allocating the budget to the CES investment.…”
Section: Approach Overview a Regulatory Considerationmentioning
confidence: 99%
“…So TSO even will give subsidies to MGs. As a case study, [40] reports assigning subsidies to an energy storage project in China with a 5 MWh lithium and a 20 MWh lead-acid energy storage system. In our study, peak shaving and annual electricity cost reduction have been considered factors for allocating the budget to the CES investment.…”
Section: Approach Overview a Regulatory Considerationmentioning
confidence: 99%
“…Yu et al used the principal-agent theory to find an optimal value of subsidy between the government and microgrid users for the energy storage. They concluded that an optimal strategy for the government is to provide tailored incentive to the microgrid users for energy storage [72]. Liang et al use the principal-agent theory for the building sector energy efficiency retrofit (EER) and explain the agency problem that exists between the government and the building owners.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang, Wang, and Chai found that government subsidies provided to new energy taxis and special vehicles have high subsidy efficiency (Zhang et al, 2020;Nie et al, 2021). Yu, Lin, and Qi found that government subsidies are more efficient when micro-grid users do not hide their private information, and the adverse selection problem reduces the subsidy efficiency (Yu et al, 2021). Decarolis, Polyakova, and Ryan found that an efficient government subsidy mechanism should have three characteristics: maintaining the marginal elasticity of demand, limiting the influence of market forces, and ensuring the link between price and marginal cost (Decarolis et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%